2017
DOI: 10.1136/gutjnl-2017-313815
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and risk stratification of Barrett’s dysplasia by flow cytometric DNA analysis of paraffin-embedded tissue

Abstract: This study demonstrates the promise of DNA flow cytometry using FFPE tissue in the diagnosis and risk stratification of dysplasia in BO. The presence of DNA content abnormality correlates with increasing levels of dysplasia, as 95% of HGD samples showed DNA content abnormality. DNA flow cytometry also identifies a subset of patients with LGD and IND who are at higher risk for subsequent detection of HGD or OAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 49 publications
2
35
1
Order By: Relevance
“…Of note, based on the published consensus guidelines, 20,21 the minimum number of cells or nuclei needed in a histogram to reproducibly detect aneuploidy is approximately 5000, which can be easily obtained from small mucosal biopsies. [14][15][16][17][18][19] The number of nuclei collected for DNA content measurements in this study ranged from 5000 to 20 000 (not including aggregates and debris), and the mean and median percentages of nuclei seen in an aneuploid population were 31 and 22% of this total, respectively (range = 6-70%).…”
Section: Materials and Methods P A T I E N T S A N D D A T A C O L L mentioning
confidence: 94%
See 1 more Smart Citation
“…Of note, based on the published consensus guidelines, 20,21 the minimum number of cells or nuclei needed in a histogram to reproducibly detect aneuploidy is approximately 5000, which can be easily obtained from small mucosal biopsies. [14][15][16][17][18][19] The number of nuclei collected for DNA content measurements in this study ranged from 5000 to 20 000 (not including aggregates and debris), and the mean and median percentages of nuclei seen in an aneuploid population were 31 and 22% of this total, respectively (range = 6-70%).…”
Section: Materials and Methods P A T I E N T S A N D D A T A C O L L mentioning
confidence: 94%
“…As previously described, [14][15][16][17][18][19] three to six 60-lm-thick sections were cut from each tissue block, and the area of CCA was manually dissected for analysis. DNA fluorescent dye DAPI (4,6-diamidino-2phenylindole; Accurate Chemical & Scientific Corporation, Westbury, NY, USA) was used to stain each specimen, which was subsequently analysed on a BD LSRII S854 flow cytometer (BD Biosciences, San Jose, CA, USA) with UV laser excitation.…”
Section: Materials and Methods P A T I E N T S A N D D A T A C O L L mentioning
confidence: 99%
“…As previously described [38,39,41], three to four 60micron thick sections were cut from each tissue block, and a potential abnormal cell population was enriched by manually dissecting the areas of dysplasia from the background normal tissue. DAPI (4,6-diamidino-2-phenylindole; Accurate Chemical & Scientific Corporation, Westbury, NY) was used to stain each sample, which was subsequently analyzed with a BD LSRII S854 flow cytometer (BD Biosciences, San Jose, CA) using UV laser excitation.…”
Section: Dna Flow Cytometrymentioning
confidence: 99%
“…As an alternative, DNA flow cytometry can potentially be useful as an adjunct method for the diagnosis and/or risk assessment of ampullary dysplasia. Although we recently demonstrated its utility in dysplasia of Barrett's esophagus [38], inflammatory bowel disease [39,40], and stomach [41], reports of such analyses on ampullary dysplasia are currently not available. Thus, this study examines the potential value of DNA content analysis in the diagnosis and/or risk stratification of ampullary dysplasia using formalin-fixed paraffin-embedded tissue obtained from endoscopic biopsies.…”
Section: Introductionmentioning
confidence: 99%
“…18q loss was found in 32% BE, 42% LGD, 73% HGD, and 69% EAC [74]. One recent study has demonstrated the potential clinical application of DNA flow cytometry in the diagnosis and risk stratification for BE patients [75].…”
Section: Genetic and Molecular Signature Of Be And Early Stage Eacmentioning
confidence: 99%